Cooperative Innovation in the Medical Supply Chain Based on User Feedback - Ran Chen; Gui-sheng Hou; Yu Wang (Complexity)
Given the importance of users in medical innovation, positive user participation can boost the cooperative innovation process within the medical supply chain. A stochastic differential model based on user feedback is proposed to study the relationship between user feedback and the medical supply chain. The stability and sensitivity of the medical supply chain is analysed through different parameters. The results show that the effect of patient feedback and suggestions from hospitals on the innovation level of medical services and medical products is positive, such that the impact of the innovation level of medical services on users and the effect of patient feedback are positively related to marginal profits and that cooperative innovation is beneficial for medical product and service innovation and the improvement of demand and profits.